Ancestral knowledge as promotion of physical and mental health: an agroecological view - Barbosa, Flávia Silva (ODEERE, 2023)
Industrial agriculture uses numerous xenobiotics that affect the human microbiome, trigger dysbiosis, and compromise neurological and neuropsychiatric development. On the other hand, ancestral eating habits indicate that dietary diversification, including vegetables and proteins, without agrochemicals, promotes mental and physical health in addition to allowing environmental balance. As a solution, ancestral knowledge must be combined with agroecology to save human health.